Constant frequency torque and flux controllers for direct torque control of induction machines - Nik Idris, Nik Rumzi (IEEE, 2003)

(untitled)
This paper proposed a simple solution to the variable switching frequency and high torque ripples problems encountered in hysteresis-based DTC drives. The method replaces the hysteresis-based controllers with fired switching controller which operate based on the comparison between the error signals and the triangular waveforms. Implementation of these coutrollen using digital circuits is highly suitable since they only require Comparisons of waveforms rather than calculations of duty cycles or voltage vectors. Modeling and simulation of the DTC drives using these simple controllers are presented and the results show that they are capable of reducing tbe torque ripples significantly.